On Rainbow Antimagic Coloring of Joint Product of Graphs - Septory, Brian Juned; Susilowati, Liliek; Dafik, Dafik; Venkatachalam, M. (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2023)
Let  be a connected graph with vertex set  and edge set . A bijection  from  to the set  is a labeling of graph . The bijection  is called rainbow antimagic vertex labeling if for any two edge  and  in path , where  and . Rainbow antimagic coloring is a graph  which has a rainbow antimagic labeling. Thus, every rainbow antimagic labeling induces a rainbow coloring G where the edge weight  is the color of the edge . The rainbow antimagic connection number of graph  is the smallest number of colors of all rainbow antimagic colorings of graph , denoted by . In this study, we studied rainbow antimagic coloring and have an exact value of rainbow antimagic connection number of joint product of graph  where  is graph , graph , graph , graph  and graph .